Suprapubic Percutaneous Assisted Cystoscopic Excision of Posterior Urethral Fibroepithelial Polyps in Pediatric Patients - Ozcakir, Esra; Kaya, Mete (Urology Journal, 2020)
Purpose: The aim of this study was to evaluate pediatric posterior urethral fibroepithelial polyps, their diagnosis and endoscopic treatments with suprapubic assisted transurethral polyp excision which is described by us. Materials and Methods: We reviewed the charts of patients (n=6) who underwent suprapubic percutaneous assisted cystoscopic excision for posterior urethral fibroepithelial polyp from 2014 to 2019. Their data were retrospectively reviewed in terms of clinical features, diagnostic methods, endoscopic approaches, and postoperative results. Results: The 6 patients, the mean age of 3 years (4 months-6 years), with a solitary polyp of posterior urethra diagnosed and removed by suprapubic percutaneous assisted cystoscopic excision in five years. The most common complaint was urinary tract infection (n:3). The urethral polyps were diagnosed by ultrasound and cystoscopy. There was no intraoperative or postoperative complication except for one patient with bleeding from the trocar site. All of the specimens after histopathology examinations showed fibroepithelial polyps and no recurrence was seen. Conclusion: Posterior urethral polyps may cause obstructive effect in the urinary tract. The treatment should be performed with the least possible invasive method without injuring urethral wall. We believe that suprapubic percutaneous assisted cystoscopic resection, described by us is an easy, reliable and effective method for treatment procedure of posterior fibroepithelial urethral polyps.